DIALECTICISMS IN THE LEXICON OF THE FOLK EPIC COMMENT - Olimova Rushana Ilgorzhan’s daughter; Khaitov Khusniddin Khasanovich (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, the pure dialectisms used in the lexicon of the folk epic are described based on the classification of the parts named "Goroguli", "Avazkhan" in the epic "Goroguli". In addition, necessary comments were given about the dialectal words given in the parts of the epic being used even today.